KEMAMPUAN KONEKSI MATEMATIS SISWA DIKAJI DARI KEMAMPUAN PENALARAN ADAPTIF DALAM MATERI KUBUS DAN BALOK - Ridwan Ridwan; Sugiatno Sugiatno; Hamdani Hamdani (Universitas Tanjungpura, 2021)
AbstractThe purpose of this study was to describe the mathematical connection ability of students studied from their adaptive reasoning ability in solving cube and block material problems in junior high school. This research was arranged in the form of a case study with the research subjects are 20 students of class IXc SMP Negeri 1 Tebas who have studied cube and block material, while the object in this research were the mathematical connection ability and adaptive reasoning abilities. Data collection in this research was carried out through tests of adaptive reasoning abilities and tests of mathematical connection abilities as well as interviews as a follow-up activity after being given the test. Based on the data analysis conducted, the results showed that students 'mathematical connection abilities tended to be in line with students' adaptive reasoning abilities. Students with high category adaptive reasoning ability tend to have high category mathematical connection ability, which is 75% of them. Students with moderate category addictive reasoning ability tend to have mathematical connection ability which is classified as moderate category, which is 76.92% of them. Meanwhile, students with low category of adaptive reasoning tend to have low mathematical connection ability, which is 67% of them.Keywords: Adaptive Reasoning, Cube and Block, Mathematical Connection